Support of Émigré and Foreign Organisations for the Catholic Church in Lithuania during the Soviet Occupation - Streikus, Arūnas (Genocidas ir rezistencija, 2006)
From the very first days of the occupation of Lithuania, the clergy who had fled to the West began actively organising support for the Catholic Church which was persecuted by the Soviet regime. In the first decades, the Lithuanian priests living in Ro- me were mostly involved in this activity. They represented the Lithuanian Catholic Church in the institutions of the Vatican, and sought to collect and disseminate information about its situation. Due to the lack of constant communication with the occupied homeland, it was at first rather complicated for the émigrés to respond to the problems of the persecuted Church and to render more support. The situation significantly changed in the seventies. First, the expanded connections resulted in a bigger flow of information about the situation of the Lithuanian congregation. Second, after the establishment of the Lithuanian Catholic Religious Aid (LCRA), there was a new and strong centre established in the USA, which defended the interests of the Lithuanian Catholic Church in the West. Third, the foreign organizations which were concerned about the situation of the congregation in the Communist block countries, including Lithuania, became active. Most notable was Keston College in England which paid particular attention to Lithuania. The support of the Holy See for the persecuted Lithuanian Catholic Church also became clearer and more concrete. As a result, the issue of the Lithuanian congregation's rights became an important factor in the domestic and foreign affairs of the Soviet Union. This is confirmed both by the documents of Soviet state institutions, which reflect concern about the increased attention of the West to the problem of religious freedom in Lithuania, and by the active efforts of the Soviet regime to counteract this factor.
Keywords: emigree; Catholic Church; resistance; USA; Great Britain